Demonstration analysis for the low-carbon factors index system of logistics enterprises - Yuan Tian; Meng Yang (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: In the background of the low-carbon economy, the basic position of the logistics and its high energy consumption, high emission characteristics determine its special status in the low-carbon economy. The purpose of this paper is providing ideas for logistics companies to implement low-carbon management. Design/methodology/approach: This paper analyses the characteristics and the processes of the logistics enterprises in China. Analyze the low-carbon management factors from the perspective of energy consumption. Then do the demonstration analysis by calculating the connection degree of the indicators and the logistics energy consumption, using the method of grey connection analysis. Findings: Establish the logistics enterprise's low-carbon management factors index system. And the connection degree is greater than 0.5, indicating that various factors impact significantly on the low-carbon management of logistics enterprises. Originality/value: The study provides ideas for logistics companies to implement low-carbon management.
Keywords: 650; logistics enterprises; low-carbon; energy consumption; grey connection analysis